Дама из Амстердама: повесть / Анна Данилова - Данилова Анна Васильевна (Детектив по Фрейду, 2006)
Экземпляры: ф.6 (20240809) / Инвентарный номер: 4276 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 18 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44